THE IMPACTS OF THE BRAZILIAN CRYPTOASSETS LAW IN NFT SOLUTIONS - Becker, Daniel; Gonçalves, Aylton (International Journal of Law in Changing World, 2023)
This article aims to establish the applicability of Law No. 14,478, enacted on December 21, 2022 (hereafter referred to as the Brazilian Cryptoassets Law), to the trading of non-fungible tokens (NFTs) that utilize Blockchain and Smart Contract technologies. The article covers (i) the use of Smart Contracts and Blockchain in relation to NFTs, (ii) the current state-of-the-art NFT solutions, and (iii) the key articles and legal obligations outlined in the Brazilian Cryptoassets Law. It’s important to note that the Brazilian Cryptoassets Law applies differently to various NFT solutions depending on their intended use, which is the distinguishing factor in determining whether the law is applicable to a particular NFT transaction.